Investigating axial diffusion in cylindrical pores using confocal single‐particle fluorescence correlation spectroscopy. Issue 15 (27th June 2016) - Chen, Fang; Neupane, Bhanu; Li, Peiyuan; Su, Wei; Wang, Gufeng
Abstract : We explored the feasibility of using confocal fluorescence correlation spectroscopy to study small nanoparticle diffusion in hundred‐nanometer‐sized cylindrical pores. By modeling single particle diffusion in tube‐like confined three‐dimensional space aligned parallel to the confocal optical axis, we showed that two diffusion dynamics can be observed in both original intensity traces and the autocorrelation functions (ACFs): the confined two‐dimensional lateral diffusion and the unconfined one‐dimensional (1D) axial diffusion. The separation of the axial and confined lateral diffusion dynamics provides an opportunity to study diffusions in different dimensions separately. We further experimentally studied 45 nm carboxylated polystyrene particles diffusing in 300 nm alumina pores. The experimental data showed consistency with the simulation. To extract the accurate axial diffusion coefficient, we found that a 1D diffusion model with a Lorentzian axial collection profile needs to be used to analyze the experimental ACFs. The diffusion of the 45 nm nanoparticles in polyethyleneglycol‐passivated 300 nm pores slowed down by a factor of ∼2, which can be satisfactorily explained by hydrodynamic frictions.